The sexuological impact of hormonal contraceptives based on their route of administration. (4th March 2017) - Guida, Maurizio; Di Carlo, Costantino; Troisi, Jacopo; Gallo, Alessandra; Cibarelli, Francesca; Martini, Ellis; Tiranini, Lara; Nappi, Rossella E.
Abstract: Evidence on the effects of hormonal contraceptives on female sexuality is conflicting. We enrolled 556 women, divided into six groups: two composed of subjects using a combined hormonal contraceptive (COC) containing 0.020 ("COC20") and 0.030 ("COC30") mg of ethynyl estradiol (EE), "natural", using COC containing 1.5 mg of estradiol (E2 ), "ring", using a vaginal ring releasing each day 0.015 mg of EE + 0.120 of etonogestrel, "subcutaneous", using a progestin only subcutaneous contraceptive implant releasing etonogestrel and "controls", using no hormonal contraceptive methods. The subjects were required to answer to the McCoy female sexuality questionnaire and were subjected to a blood test for hormonal evaluation. An ultrasound evaluation of the dorsal clitoral artery was also performed. The higher McCoy sexological value were recorded in the subdermal group; significant differences were recorded among the groups in terms of hormone distribution, with the higher levels of androstenedione in subdermal and control groups. The ultrasound evaluation of dorsal clitoral artery shows a significative correlation between pulsatility and resistance indices and orgasm parameters of McCoy questionnaire. The recorded difference in the sexual and hormonal parameters among the studied hormonal contraceptives may guide toward the personalization of contraceptive choice.